Prevalence of non Helicobacter pylori gastric Helicobacters in Iranian dyspeptic patients - Shafaie, Shakiba (BMC Gastroenterol, 2020)
BACKGROUND: Non Helicobacter pylori gastric Helicobacters (NHPGHs) are associated with a range of upper gastrointestinal symptoms, histologic and endoscopic findings. For the first time in Iran, we performed a cross-sectional study in order to determine the prevalence of five species of NHPGHs in patients presenting with dyspepsia. METHODS: The participants were divided into H. pylori-infected and NHPGH-infected groups, based on the rapid urease test, histological analysis of biopsies, and PCR assay of ureA, ureB, and ureAB genes. The study included 428 gastric biopsies form dyspeptic patients, who did not receive any treatment for H. pylori. The samples were collected and sent to the laboratory within two years. H. pylori was identified in 368 samples, which were excluded from the study. Finally, a total of 60 non-H. pylori samples were studied for NHPGH species. RESULTS: The overall frequency of NHPGH species was 10 for H. suis (three duodenal ulcer, three gastritis, and four gastric ulcer samples), 10 for H. felis (one gastritis, three duodenal ulcer, and six gastric ulcer samples), 20 for H. salomonis (four duodenal ulcer, five gastritis, and 11 gastric ulcer samples), 13 for H. heilmannii (three gastritis, five duodenal ulcer, and five gastric ulcer samples), and 7 for H. bizzozeronii (zero gastric ulcer, two duodenal ulcer, and five gastritis samples). CONCLUSIONS: Given our evidence about the possibility of involvement of NHPGHs in patients suffering from gastritis and nonexistence of mixed H. pylori infection, bacteriological testing of subjects negative for H. pylori becomes clinically relevant and important. Our findings suggest H. salomonis has the highest rate among the NHPGH species in Iranian dyspeptic patients.